Contending visions of the Middle East : the history and politics of Orientalism - Lockman, Zachary (Cambridge, UK : Cambridge University Press, 2010)
'Zachary Lockman's informed and thoughtful history of European Orientalism and U.S. Middle East studies, the'clash of civilizations' debate and America's involvement in the region has become a highly recommended and widely used text since its publication in 2004. The second edition of Professor Lockman's book brings his analysis up to date by considering how the study of the Middle East has evolved in the intervening years, in the context of the U.S. occupation of Iraq and the'global war on terror''--Provided by publisher.
'Zachary Lockman's informed and thoughtful history of European Orientalism and U.S. Middle East studies, the'clash of civilizations' debate and America's involvement in the region has become a highly recommended and widely used text since its publication in 2004. The second edition of Professor Lockman's book brings his analysis up to date by considering how the study of theMiddle East has evolved in the intervening years, in the context of the U.S. occupation of Iraq and the'global war on terror'. ZACHARY LOCKMAN teachesmodernMiddle Eastern history atNew York University. His previous publications include Comrades and Enemies: Arab and Jewish Workers in Palestine, 1906-1948 (1996). He has served as president of the Middle East Studies Association, speaks and writes widely on current events in the Middle East and U.S. foreign policy, and is a contributing editor of Middle East Report. i'--Provided by publisher.
Includes bibliographical references (p. 301-311) and index.
Keywords: Orientalism; Islam -- 20th century; Middle East -- Study and teaching